2014
DOI: 10.1366/13-07292
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Correction of Turbidity Effects on Raman Observations of Chemicals in Aqueous Solutions

Abstract: Improvements in diode laser, fiber optic, and data acquisition technologies are enabling increased use of Raman spectroscopic techniques for both in lab and in situ water analysis. Aqueous media encountered in the natural environment often contain suspended solids that can interfere with spectroscopic measurements, yet removal of these solids, for example, via filtration, can have even greater adverse effects on the extent to which subsequent measurements are representative of actual field conditions. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…According to Sinfield et al. 29 the turbidity can be found in the Raman signal since the reciprocal of the Raman water signal measured at the OH stretching band varies directly with the beam attenuation by turbidity. In this study, the turbidity was computed from Raman measurements by integrating the peak area in the range of 3100–3300 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sinfield et al. 29 the turbidity can be found in the Raman signal since the reciprocal of the Raman water signal measured at the OH stretching band varies directly with the beam attenuation by turbidity. In this study, the turbidity was computed from Raman measurements by integrating the peak area in the range of 3100–3300 cm –1 .…”
Section: Methodsmentioning
confidence: 99%
“…To observe the formation of microgel particles during precipitation polymerization, the change in turbidity during reaction was measured using the integrated turbidity sensor in the Mettler-Toledo RC1su Reaction Calorimeter as well as by integration of the Raman water signal. According to Sinfield et al 29 the turbidity can be found in the Raman signal since the reciprocal of the Raman water signal measured at the OH stretching band varies directly with the beam attenuation by turbidity. In this study, the turbidity was computed from Raman measurements by integrating the peak area in the range of 3100-3300 cm -1 .…”
Section: Turbidity Measurementsmentioning
confidence: 99%
“…For use with MM cultures and other situations, such an association would be required to implement a BSN training set based on using Raman features as the IE. Relevant results are available in the Supplemental Material for this paper, but we will discuss the effects of turbidity induced spectral distortion [49][50][51] in constructing Raman based BSN training sets in detail in a separate publication. We used 101-7 baselinecorrected raw data for 900-1902 cm À1 to minimize the fluorescence contribution.…”
Section: Results: Known Artifacts and Internal Consistencymentioning
confidence: 99%
“…The choice of substrate is significant in that one must be sure the substrate itself does not provide a Raman return intensity on par with that of the desired sample. While analysis of simple solutions is straightforward, analysis of turbid liquids (e.g., biologic fluids and natural water samples) may require use of specialized corrections to enable quantitative evaluation [13]. Raman can also be performed on gases, but detection is often more challenging due to the reduced molecular density of this form of matter.…”
Section: The Samplementioning
confidence: 99%